2020
DOI: 10.1101/2020.08.19.258541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-scale mapping reveals complex regulatory activities of RpoN inYersinia pseudotuberculosis

Abstract: RpoN, an alternative sigma factor commonly known as sigma 54, is implicated in persistent stages of Yersinia pseudotuberculosis infections in which genes associated with this regulator are upregulated. We here combined phenotypic and genomic assays to provide insight into its role and function in this pathogen. RpoN was found essential for Y. pseudotuberculosis virulence in mice, and in vitro functional assays showed that it controls biofilm formation and motility. Mapping genome-wide associations of Y. pseudo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Our results indicate that mutation of mnmE can substantially delay phage replication; however, the exact mechanism warrants further investigation. For RpoN, an RNA polymerase factor sigma-54 which regulates the transcription of genes across diverse cellular functions 25, 26, 27, 28 , a previous study reported its association with phage resistance in Pseudomonas aeruginosa 29 . With the diverse regulatory roles played by RpoN, the specific mechanism for its association with phage infection is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that mutation of mnmE can substantially delay phage replication; however, the exact mechanism warrants further investigation. For RpoN, an RNA polymerase factor sigma-54 which regulates the transcription of genes across diverse cellular functions 25, 26, 27, 28 , a previous study reported its association with phage resistance in Pseudomonas aeruginosa 29 . With the diverse regulatory roles played by RpoN, the specific mechanism for its association with phage infection is unknown.…”
Section: Resultsmentioning
confidence: 99%